Cross-Cultural Encounters of Expatriate Women in Chitra Banerjee Divakaruni’s Oleander Girl - Subramanian, Chandra; Nathan, P. Arockia (Journal of Neonatal Surgery, 2025)
This essay examines how immigrant women’s sensitivities and identity formation in the cross-cultural confines of the exotic land are related to Chitra Banerjee Divakaruni’s Oleander Girl (2013). It is a new, exciting, coming-of-age story about a young woman who lives in India but moves to America in quest of her identity, which changes her life. With a cross-cultural backdrop, this novel provides a broad overview of the protagonists’ sociocultural experiences in both India and America. Divakaruni has thought about the necessity of interpreting her community’s situation by portraying the experiences of Indian women in America. She depicts the conflicts faced by Indians who have left their homeland and attempt to maintain their cultural identity while assimilating into their new country.